The Effects of Storage and Sterilization on De-Cellularized and Re-Cellularized Whole Lung - Bonenfant, Nicholas R. (2013)
Despite growing interest on the potential use of de-cellularized whole lungs as 3-dimensional scaffolds for ex vivo lung tissue generation, optimal processing including sterilization and storage conditions, are not well defined. Further, it is unclear whether lungs need to be obtained immediately or may be usable even if harvested several days post-mortem, a situation mimicking potential procurement of human lungs from autopsy. We therefore assessed effects of delayed necropsy, prolonged storage (3 and 6 months), and of two commonly utilized sterilization approaches: irradiation or final rinse with peracetic acid, on architecture and extracellular matrix (ECM) protein characteristics of de-cellularized mouse lungs. These different approaches resulted in significant differences in both histologic appearance and in retention of ECM and intracellular proteins as assessed by immunohistochemistry and mass spectrometry. Despite these differences, binding and proliferation of bone marrow-derived mesenchymal stromal cells (MSCs) over a one month period following intratracheal inoculation was similar between experimental conditions. In contrast, significant differences occurred with C10 mouse lung epithelial cells between the different conditions. Therefore, delayed necropsy, duration of scaffold storage, sterilization approach, and cell type used for re-cellularization may significantly impact the usefulness of this biological scaffold-based model of ex-vivo lung tissue regeneration.